Increased bone accrual in premenarcheal gymnasts: A longitudinal study - Gero, N.; Cole, J.; Kanaley, J.; van der Meulen, M.; Scerpella, T. (Pediatric Exercise Science, 2005)
This longitudinal study evaluates the role of impact activity in bone accrual in premenarcheal girls. Twenty-eight gymnasts and 20 controls underwent 1-year analysis; fifteen gymnasts and 8 controls underwent 2-year analysis. Bone mineral density (BMD) was measured yearly by dual energy X-ray absorptiometry. For the 1-year analysis, BMD accrual rates were greater in gymnasts than controls at the forearm only (p < .05). For the 2-year analysis, gains in BMD were 1.5 to 1.9 times greater at the forearm, total hip, and femoral neck for gymnasts (p < .05). These findings confirm the positive effect of impact activity on bone accrual in premenarcheal girls.